Класифікація гірських ландшафтів Українських Карпат і перспективи розвитку пішохідного туризму в регіоні = Classification of mountain landscapes of Ukrainian Carpathians and the prospects of developing walking tourism in the region - Melnyk, Anatolij (Journal of Education, Health and Sport, 2016)
Melnyk A. Класифікація гірських ландшафтів Українських Карпат і перспективи розвитку пішохідного туризму в регіоні = Classification of mountain landscapes of Ukrainian Carpathians and the prospects of developing walking tourism in the region. Journal of Education, Health and Sport. 2016;6(2):316-324. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47033 http://ojs.ukw.edu.pl/index.php/johs/article/view/3413 https://pbn.nauka.gov.pl/works/718160 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. УДК 911.2:551 КЛАСИФІКАЦІЯ ГІРСЬКИХ ЛАНДШАФТІВ УКРАЇНСЬКИХ КАРПАТ І ПЕРСПЕКТИВИ РОЗВИТКУ ПІШОХІДНОГО ТУРИЗМУ В РЕГІОНІ CLASSIFICATION OF MOUNTAIN LANDSCAPES OF UKRAINIAN CARPATHIANS AND THE PROSPECTS OF DEVELOPING WALKING TOURISM IN THE REGION А. Мельник A. Melnyk Uniwersytet Kazimierza Wielkiego, Bydgoszcz Kazimierz Wielki University, Bydgoszcz Abstract A genetic classification of mountain landscapes of Ukrainian Carpathians mountains is presented on the basic of azonal approach, which is based on the use of geological and geomorphological characteristics, the main sources of landscape genesis and development. The method of combining landscapes into higher classification categories and the method of dividing higher categories into lower ones have been used. Such classification categories of landscapes type, kind, family and subclass. Mountain landscapes of Ukrainian Carpathians have been united into 13 kinds, 6 families and 5 subclasses. As for being favourable for the development of walking tourism, the landscapes are divided into 4 categories: the most favourable, rafher favourable, weakly favourable and the least favourable. Keywords: mountain landscapes, landscape classification, walking tourism, Ukrainian Carpathians. Анотація Представлено генетичну класифікацію гірських ландшафтів Українських Карпат на основі азонального підходу, який базується на використанні геолого-геоморфологічних ознак – головних чинників генезису і розвитку ландшафтів. Використано метод об’єднання ландшафтів у вищі класифікаційні категорії та метод поділу вищих категорій на нижчі. Запропоновано такі класифікаційні категорії ландшафтів як вид, рід, родина і підклас. Гірські ландшафти Українських Карпат об’єднано у 13 родів, 6 родин і 5 підкласів. За ступенем сприятливості для розвитку пішохідного туризму ландшафти поділено на 4 категорії: найбільш сприятливі, достатньо сприятливі, слабо сприятливі і найменш сприятливі. Ключові слова: гірські ландшафти, класифікація ландшафтів, пішохідний туризм, Українські Карпати.